Efeito das técnicas de full-mouth disinfection e raspagem e alisamento radicular por quadrante na halitose em indivíduos com periodontite crônica avançada: ensaio clínico randomizado controlado - Juliana Oliveira da Silveira (2014)
In recent years, several studies have shown that the levels of volatile sulfur compounds are higher in patients with periodontitis. However, the relationship between periodontal disease and bad breath is still controversial in relation to the severity, the influence of risk variables, and the treatment of choice. The objective of this randomized controlled trial was to evaluate the effect of the conventional scaling and root planing per quadrant (RAR-Q) compared to one-stage full-mouth disinfection (FMD) on halitosis, in patients with advanced chronic periodontitis. In this manner, 30 patients with advanced chronic periodontitis were selected from periodontics clinics at the Department of Dentistry of Pontiphical Catholic University of Minas Gerais from April 2013 to May 2014. A complete periodontal clinical examination was performed and the following parameters were recorded: probing depth (PD), clinical attachment level (CAL), bleeding on probing, plaque index, and tongue coating index. Halitosis assessment using the organoleptic method and the measurement of volatile sulfur compounds (VSC), including hydrogen sulfide (H2S) and methyl mercaptan (CH3SH) from gas chromatography, at baseline and 90 days after non-surgical periodontal treatment, were performed. After periodontal clinical examination, individuals were randomly allocated in the FMD group, which was submitted to a one-stage full-mouth disinfection therapy, and the RAR-Q group, which was submitted to scaling and root planing per quadrant. To compare halitosis and the quantification of sulfur gases, the Mann-Whitney and Wilcoxon tests were used. For inter- and intra-group categorical variables NIC, PS, H2S and CH3SH comparisons, the Chi-squared, McNemar, and Fisher exact tests were used, when appropriate. Findings showed that the non-surgical periodontal treatment, independently from the therapy used, resulted in significant improvement of clinical periodontal parameters. The assessment of halitosis from the organoleptic method showed that the FMD group had significant reduction of halitosis scores from baseline to final examinations (p = 0.015). Gas chromatography showed no significant intra- and inter-group difference in the concentration of volatile sulfur compounds.